Exploring identity crisis in A House for Mr. Biswas from a post-colonial perspective - Md. Jony Miah; Farjana Yasmin Meem; Rakib Al Hasan (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
This paper explores the post-colonial themes of identity crisis, alienation, and cultural displacement in V.S. Naipaul’s A House for Mr. Biswas. Through a close reading of the novel, the study examines how the protagonist, Mr. Biswas, resists the oppressive control of the Tulsi family and asserts his individuality by striving to build a house of his own. Rather than conforming to the familial imperialism that mirrors colonial dominance, Mr. Biswas challenges it, making his pursuit of a home a powerful metaphor for post-colonial resistance and self-definition. The analysis highlights how Naipaul portrays the existential struggles of a marginalized individual within a fractured society shaped by colonial legacy. Using descriptive and analytical methods, with the novel as the primary source and scholarly literature as secondary support, this study reveals that Mr. Biswas’s journey is emblematic of the broader post-colonial quest for autonomy and identity. Ultimately, the novel affirms that reclaiming personal space is essential to overcoming cultural subjugation and achieving post-colonial liberation.